Genome-wide analysis of TPX2 gene family in Populus trichocarpa and its specific response genes under various abiotic stresses - Qi, Meng; Wang, Shengjie; Li, Na; Li, Lingfeng; Zhang, Yue; Xue, Jingyi; Wang, Jingyi; Wu, Rongling; Lian, Na (Frontiers in Plant Science, 2023)
Microtubules are essential for regulating cell morphogenesis, plant growth, and the response of plants to abiotic stresses. TPX2 proteins are the main players determining the spatiotemporally dynamic nature of the MTs. However, how TPX2 members respond to abiotic stresses in poplar remains largely unknown. Herein, 19 TPX2 family members were identified from the poplar genome and analyzed the structural characteristics as well as gene expression patterns. All TPX2 members had the conserved structural characteristics, but exhibited different expression profiles in different tissues, indicating their varying roles during plant growth. Additionally, several light, hormone, and abiotic stress responsive cis-acting regulatory elements were detected on the promoters of PtTPX2 genes. Furthermore, expression analysis in various tissues of Populus trichocarpa showed that the PtTPX2 genes responded differently to heat, drought and salt stress. In summary, these results provide a comprehensive analysis for the TPX2 gene family in poplar and an effective contribution to revealing the mechanisms of PtTPX2 in the regulatory network of abiotic stress.